Professor Ron K. Pickerill and the genesis of ichnology in the Antilles (Jamaica and Carriacou) - Donovan, Stephen K. (Atlantic Geoscience, 2015)
Antillean ichnology was essentially a blank book when Ron Pickerill of the University of New Brunswick, Fredericton, made his first research visit to Jamaica in February 1990. Ron’s first Jamaican trace-fossil research team worked initially on the Paleogene Richmond Formation, a flysch succession. Subsequent fieldwork examined the diverse sedimentary formations of the Neogene Coastal Group. Ron’s encyclopaedic knowledge of ichnotaxonomy and his enthusiasm for fieldwork led the team in many directions. Investigations were integrated with new studies of the island’s sedimentology and paleontology. For example, the description of the ichnology and sedimentology of the Upper Pliocene Bowden Formation, including the internationally famous Bowden shell bed, was part of a much wider study. The case-hardened rocks of the White Limestone Group discouraged detailed study until Donovan Blissett attacked the diverse ichnobiota of these user-unfriendly rocks for his doctorate under Ron’s supervision at the University of New Brunswick. Carriacou in the Grenadines was the other island to receive detailed examination in terms of its ichnofauna by Ron and his co-workers. The east coast of this small island provides a near-continuous exposure of the deep water succession of the Grand Bay Formation. Deeper-water burrows and borings in allochthonous bioclasts derived from the shallow shelf provide ichnological contrast in this formation.